Elevated hematologic ratios are correlated with acne severity: a national, retrospective cohort study - Wiesel, Vered; Weissmann, Sarah; Cohen, Bracha; Golan-Tripto, Inbal; Horev, Amir (Frontiers in Medicine, 2024)
Background: Prior studies demonstrated conflicting results regarding hematologic ratios in acne patients. We sought to further characterize hematologic ratios in acne patients, according to demographics and acne severity. Methods: National, retrospective cohort study of 122,822 patients using medical records from 2005-2024 of patients insured with the largest public healthcare organization in Israel, Clalit Health Maintenance Organization. Results: Moderate-severe acne patients had higher neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) than mild acne patients at diagnosis and 12-18 months before diagnosis. A multivariable regression confirmed the significance of the correlation of increased NLR and PLR with acne severity. Adults and females had higher NLR and PLR than children and males, respectively, at diagnosis, and 12-18 months before diagnosis. Conclusion: Acne severity was significantly associated with elevated NLR and PLR. NLR and PLR may also serve as indicators of upcoming acne severity, as they were elevated 12-18 months before diagnosis. These biomarkers may contribute to the diagnosis, management, and follow-up of patients with acne.